2012
DOI: 10.15282/jmes.2.2012.5.0016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice Husks as Filler in Polymer Matrix Composites

Abstract: In this study, rice husk-filled polyester composites were produced with rice husks (RH) as the filler and unsaturated polyester resin (UPR) as the matrix. Several percentages of filler loadings were used (10, 15, 20 and 25 wt %) in order to gain insights into the effect of filler content on the mechanical properties and water intake of the composites. The tensile strength of the RH-filled UPR composites was found to decrease as the filler loading increased; however, as it reached 25 wt %, the strength showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 11 publications
3
47
0
1
Order By: Relevance
“…Natural fibre has unique characteristics and many outstanding advantages over synthetic fibre, which make it an attractive alternative to traditional materials [1,2]. Natural fibres such as hemp, flax, abaca, sisal, jute, henequen, kenaf, ramie, sugar palm, oil palm, pineapple leaf, banana pseudo-stem, sugarcane bagasse, coir, rice husk, wood, bamboo, chicken feathers, wool, silk and cotton have been reported as being used as fibre in polymer composites [3][4][5][6][7][8][9]. Natural fibrereinforced plastics are gaining more attention from researchers and industry due to their cost-effectiveness, lighter weight, lower abrasion of equipment and renewability, among the several benefits of natural fibre composites [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibre has unique characteristics and many outstanding advantages over synthetic fibre, which make it an attractive alternative to traditional materials [1,2]. Natural fibres such as hemp, flax, abaca, sisal, jute, henequen, kenaf, ramie, sugar palm, oil palm, pineapple leaf, banana pseudo-stem, sugarcane bagasse, coir, rice husk, wood, bamboo, chicken feathers, wool, silk and cotton have been reported as being used as fibre in polymer composites [3][4][5][6][7][8][9]. Natural fibrereinforced plastics are gaining more attention from researchers and industry due to their cost-effectiveness, lighter weight, lower abrasion of equipment and renewability, among the several benefits of natural fibre composites [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The result of weak bonding between the water absorbing filler and the water resistant matrix polymer obstructs the stress propagation, and thus reduce the tensile strength when the filler loading increases. In addition, poor dispersion results in filler clouding and drops in tensile properties (Hardinnawirda and Sitirabiatull, 2012). Maximum tensile strength of 13.2Mpa is noticed with 2 nd sample i.e., 5% filler.…”
Section: Tensile Testmentioning
confidence: 98%
“…Hardinnawirda and Aisha [16] reported that the tensile strength of the rice husk composites moderate increased for the 25 wt% filler loading, the values ranged between 12-16 MPa. Meanwhile in this study the tensile strength was obtained between 32.53 -36.26 MPa at fiber weight fraction 20 -30%.…”
Section: A Tensile Propertiesmentioning
confidence: 99%